Associations of objectively assessed physical activity and sedentary time with health-related quality of life among colon cancer survivors - Vallance, J.; Boyle, Terry; Courneya, K.; Lynch, B. (John Wiley & Sons, Inc., 2014)
BACKGROUND: The primary purpose of this study was to determine associations of accelerometer-assessed moderate- to vigorousintensity physical activity (MVPA) and sedentary time with health-related quality of life (HRQoL) and physical function and well-being in colon cancer survivors. METHODS: Colon cancer survivors (N=178) from Alberta, Canada (n=92) and Western Australia (n=86) completed a mailed survey that assessed HRQoL (Functional Assessment of Cancer Therapy-Colorectal), physical function and wellbeing (Trial Outcome Index-Colorectal), and relevant covariates. MVPA and sedentary time were assessed using the Actigraph GT3X1 accelerometer (60-second epochs) via a 7-day monitoring protocol. Average daily MVPA and sedentary time was corrected for wear time and then examined as quartiles. RESULTS: Adjusting for relevant demographic, behavioral, and clinical covariates, a significant difference in HRQoL scores emerged between quartile 1 (Q1) and Q4 (Mdiff=11.5, P=.038). For physical function and wellbeing, a significant difference emerged between Q1 and Q4 (Mdiff=9.1, P=.009). For fatigue, a significant difference emerged between Q1 and Q4 (Mdiff=7.1, P=.05). Significant differences were also observed for between Q1 and Q3 (Mdiff=2.4, P=.041), and Q1 and Q4 (Mdiff=3.5, P=.002) for colorectal cancer-specific symptoms. There were no statistically significant associations of sedentary time with HRQoL, physical function and well-being, fatigue, or colorectal cancer-specific symptoms. CONCLUSIONS: Objectively measured MVPA, but not sedentary time, was associated with better HRQoL, physical function and well-being, and colorectal cancer- specific symptoms in colon cancer survivors. For MVPA, differences met or exceeded contemporary cutpoints for determining clinically important differences.